2007
DOI: 10.1021/ma062453f
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulation of Poly(dimethylsiloxane):  Force Field Development, Structure, and Thermodynamic Properties of Polymer Melt and Solubility of n-Alkanes, n-Perfluoroalkanes, and Noble and Light Gases

Abstract: Poly(dimethylsiloxane) (PDMS) is a widely used polymer for a number of industrial applications. In order that PDMS is selected for a specific application, accurate knowledge of its physical properties is necessary. Physical properties can be either measured or calculated based on reliable suitable methods. Molecular simulation using realistic models is a powerful tool for the elucidation of microscopic structure of polymers and the subsequent estimation of macroscopic physical properties. In this work, a force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 50 publications
4
33
0
Order By: Relevance
“…In the UA representation, hydrogen atoms in the methyl and methylene groups are not accounted explicitly, thus reducing the number of "atoms" significantly. Details on the force field development and parameters for the various terms and UAs can be found in refs [11][12][13]. A brief description is given here only.…”
Section: Atomistic Force-fieldmentioning
confidence: 99%
See 3 more Smart Citations
“…In the UA representation, hydrogen atoms in the methyl and methylene groups are not accounted explicitly, thus reducing the number of "atoms" significantly. Details on the force field development and parameters for the various terms and UAs can be found in refs [11][12][13]. A brief description is given here only.…”
Section: Atomistic Force-fieldmentioning
confidence: 99%
“…The initial configurations were obtained using the Cerius 2 software package of Accelrys Inc. and relaxed with molecular mechanics before MD [11,13]. MD simulations were performed with an integration time step of 0.5 fs to ensure system stability over time.…”
Section: Molecular Simulation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent molecular simulations and force field development have indicated that computational methods can offer significant insight into the behavior of surfaces [1], polyethoxy [2] and polysilicone [3] systems, hydrogen bonding [4], solvent-water interactions [5], and alkane properties [6]. Of particular interest are several studies which treat mixing thermodynamically [7], as well as those discussing the source of the hydrophobic effect [8].…”
Section: Introductionmentioning
confidence: 99%